Analisis Peran Pemerintah dalam Mengupayakan Pencegahan Stunting Untuk Mewujudkan Sumber Daya Manusia yang Berkualitas di Kecamatan Ampek Angkek - Tito Andryansyah; Sandra Dewi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Study "Analysis of the Government's Role in Efforts to Prevent Stunting to Create Quality Human Resources in Ampek Angkek District". Theoretically, this study is driven by the quality of human resources, which is quite crucial in determining economic development. Since economic development follows the rise in human resources. By examining the government's involvement in trying to avoid stunting to produce excellent human resources in the Ampek Angkek sub-district which transpires in the past, data from the research field indicates the other direction. This kind of research is field case study research using a descriptive qualitative methodology which analyzes data using interview techniques, documentation and other sources carried out at the sub-district government and numerous cross-sectors in the Ampek Angkek sub-distinct. Based on the findings of the research and data analysis that has been conducted, it can be concluded that there are several shortcomings, mainly: 1. The role of government and cross-sectors has been carried out in accordance with their roles and duties, but there may be shortcomings that have not been optimal, such as uniting cross-sectors that have not been implemented or generating convergence. 2. Insufficient facilities and TPK not proportionate for the size of the region to overcome stunting cases 3. Insufficient information, understanding, or community involvement in helping to avoid stunting.